Peningkatan Kemampuan Critical Thinking Siswa SMA Fons Vitae 1 Melalui Pelatihan Penulisan Review Film - Putri Rindu Kinasih (Lembaga Pengembangan Kinerja Dosen, 2026)
Critical thinking is an important competency that needs to be developed in students in the digital age. However, various technological disruptions and fast-paced information consumption habits can hinder students' ability to conduct in-depth analysis and evaluation. Therefore, this community service activity aims to improve the critical thinking and English writing skills of Fons Vitae 1 Senior High School students through film review writing training. The activity took place on April 23, 2026, involving 20 participants from the English Club. The implementation method combined lectures, a screening of the short film “Jalanin Aja” by Joko Anwar, discussions, film review writing practice, and evaluation using a feedback questionnaire. The results of the activity showed that 95% of participants agreed that writing film reviews can improve their critical thinking skills. Furthermore, 90% of participants felt more confident expressing their opinions through writing, 90% considered the selected films relevant to their lives, and 95% stated that the activity was fun. Thus, film review writing training has proven to be an effective learning strategy for developing students' critical thinking and English writing skills.